2022
DOI: 10.3389/fendo.2022.1026791
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-glutamyl transferase to high-density lipoprotein cholesterol ratio: A valuable predictor of type 2 diabetes mellitus incidence

Abstract: BackgroundGamma-glutamyl transferase (GGT) and high-density lipoprotein cholesterol (HDL-C) have been proven to be valuable predictors of type 2 diabetes mellitus (T2DM). The aim of this study was to investigate the association between GGT/HDL-C ratio and incident T2DM.MethodsThe study retrospectively analyzed 15453 participants from 2004 to 2015. Cox proportional hazards regression models and Kaplan-Meier curves were used to elucidate the effect of GGT/HDL-C ratio on T2DM. Restricted cubic spline (RCS) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 39 publications
(56 reference statements)
0
9
0
2
Order By: Relevance
“…While the role of GGT/HDL-C ratio in MetS resolution is novel, existing studies support its utility as a predictor of cardiometabolic diseases. 17 Chinese studies have linked elevated GGT/HDL-C ratios with an increased risk of T2DM and found its predictive performance for T2DM superior to that of GGT and HDL-C individually. 17 , 18 Furthermore, a one-unit increase in the GGT/HDL-C ratio corresponded to a 0.4% and 0.5% increase in the prevalence of NAFLD and MetS, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of GGT/HDL-C ratio in MetS resolution is novel, existing studies support its utility as a predictor of cardiometabolic diseases. 17 Chinese studies have linked elevated GGT/HDL-C ratios with an increased risk of T2DM and found its predictive performance for T2DM superior to that of GGT and HDL-C individually. 17 , 18 Furthermore, a one-unit increase in the GGT/HDL-C ratio corresponded to a 0.4% and 0.5% increase in the prevalence of NAFLD and MetS, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators suggest that elevated serum GGT reflects oxidative stress and chronic inflammation, which also contributes to the development of MetS ( 45 , 46 ). GGT not only positively correlates with numerous inflammatory factors such as C-reactive protein and interleukin-6, but also itself mediates the conversion of leukotriene C4 to leukotriene D4, which enhances the development of inflammation ( 15 ). Numerous previous studies have demonstrated that GGT is a useful biomarker for predicting MetS and its components, and that the risk of MetS increases with increasing levels of GGT ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is a risk factor for MetS, and reduced HDL-C is the most common clinical disorder of lipid metabolism. As part of the diagnosis of MetS, HDL-C can improve cellular uptake of glucose in skeletal muscle cells and insulin secretion from beta cells and helps protect β-cells from apoptosis caused by cholesterol accumulation by promoting cholesterol efflux ( 15 , 16 ). HDL-C also has anti-inflammatory and antioxidant effects, directly increasing beta cell survival by inhibiting apoptosis caused by oxidized LDL-C and inflammatory factors, HDL-C decreased levels may reflect reduced beta cell function and insulin resistance ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have shown that combining GGT with HDL-C can improve the identification of nonalcoholic fatty liver disease (NAFLD) ( 13 15 ) and type 2 diabetes mellitus (T2DM) ( 16 18 ). The GGT/HDL-C ratio was found to be closely linked to NAFLD and T2DM and was a better predictor than a single indicator.…”
Section: Introductionmentioning
confidence: 99%